Post-chemotherapy cognitive dysfunction in women with breast cancer - Gorica Vuksanović; Jelena Marić; Olivera Kalajdžić; Ivana Zečević; Sandra Matovic; Siniša Ristić (Биомедицинска истраживања, 2022)
Cancer-related cognitive dysfunction is an important clinical prob em that can interfere with the daily functioning, work productivi ty, childcare, and other responsibilities of women with a history of breast cancer. Risks of cancer-related cognitive impairment include cancer and cancer treatment, as well as patient-related vulnerabil ities. There is no established standard of neuroprotective care or treatment for breast cancer-related cognitive impairment.
Keywords: cancer-related cognitive impairment; breast cancer; women